Enhanced removal of β-lactam antibiotics from synthetic wastewater via bioaugmentation of MBBR by MBL-positive Pseudomonas aeruginosa - Mohammad Javad Shokoohizadeh; Seyyed Alireza Mousavi; Samira Khamutian; Ali Almasi (Desalination and Water Treatment)
The presence of antibiotic residues in the environment raises concerns about toxicity to aquatic organisms and the emergence and development of antibiotic-resistant bacteria. This experimental study investigated the removal efficiency of the antibiotics cephalexin and ceftriaxone from synthetic wastewater using bioaugmentation in a laboratory-scale moving bed biofilm reactor. The bioaugmentation was performed with metallo- β-lactamase-producing Pseudomonas aeruginosa to enhance antibiotic degradation. The study examined the effects of two key factors: initial antibiotic concentrations (15, 30, and 45 mg/L) and hydraulic retention times (HRT) of 4, 8, and 12 h (hr). Results showed that bioaugmentation significantly improved the removal efficiency of both antibiotics. The highest removal rates were achieved at an HRT of 12 hr and an antibiotic concentration of 30 mg/L, with 90 % removal for cephalexin and 73 % for ceftriaxone. These findings suggest that bioaugmentation of MBBR with metallo-β-lactamase-producing P. aeruginosa is an effective and economical method for eliminating β-lactam antibiotics from contaminated wastewaters, such as those from pharmaceutical and hospital sources. This approach offers a promising solution to reduce antibiotic residues in the environment, thereby mitigating antibiotic potency in aquatic environments and the spread of antibiotic-resistant bacteria.